Analysis Of The Effect Of Digital Transformation On Smes Around Unimed - Mica Siar Meiriza; Abim Khaffi Maulana; Enzi Anatasya Sembiring; Etri Br Kaban; Salamah Tumangger (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
From a global viewpoint, the business climate is unpredictable and competitive due to external causes, the majority of which are technological change generators. The purpose of this study is to determine the impact of technology on SMEs in the city of Medan. The samples were gathered from small and medium-sized firms (SMEs) in the UNIMED area. With a qualitative design, this study collects data through semi-structured interviews with eight enterprises in the UNIMED area. Interviews were transcribed following data collection to identify common themes. This study highlighted themes such as